(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The article aims to link the contents of the latest collection of essays by Giorgio Chittolini, La Chiesa lombarda. Ricerche sulla storia ecclesiastica dell’Italia padana (secoli XIV-XVI) (2021), to the research routes promoted by the author during the past decades, thanks to the work of a large contingent of scholars. A massive campaign, in fact, was undertaken to characterize the late-medieval phase of Italian Church’s history, without reducing its character from the viewpoint of the Counter-Reformation, or the failed Reformation, and above all renouncing the abused category of decline. Therefore, the specific functioning of ecclesiastical institutions and the close relationship established in this period between the Church, the Italian lords and the social elites were studied. The careers of ecclesiastics, studied with a prosopographical approach, the activity of the diocesan curias – with inputs into the issues of documentary systems and judicial settlement of disputes –, the territorial structures of the Church are some areas of this research. The polycentric feature of Lombardy was thus outlined: able to intervene variously on the wealth and offices of the Church were the papal court, the duke and his entourage, the elites of Milan, and of the other cities and towns. This polycentric framework was further articulated thanks to the attention dedicated to the ability of even the smaller communities to construct their own identity by acting for the founding and smooth running of the parish. More recently scholars’ attention has broadened to the religious culture, not only of the elites, in which a large part had an experience of the supernatural based on ritual efficacy, but in which even more intense devotional impulses were active. From this perspective, it was possible to go beyond the stereotypes and shortcomings already denounced by contemporaries (the institutional uncertainties, the lay hoarding of Church’s goods and rights, the ignorance of the lower secular clergy and the fall of monastic ideals, the lukewarm faith of worshipers and so on), and thus understand how this ecclesiastical world was capable of responding to a peculiar sense of the sacred.